TEKNIK TONGUING DAN VIBRATO SAXOPHONE ALTO PADA LAGU BE. NO 720 NAENG MARSINONDANG NGOLUNGKU DI GEREJA HKBP LUMBAN SIAGIAN - Bobby Lumban Tobing; Robert KA. Simangunsong; Boho Parulian Pardede; Roy JM. Hutagalung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the application of playing techniques, specifically tonguing and vibrato, on the alto saxophone in performing the song Buku Ende (BE) No. 720